Health Sector Financing: Empirical Analysis of the Evolution of the Ratio between Public and Private Financing in Developed Economies - Alcina NUNES; Célia VAZ; Jorge ALVES (Communications of International Proceedings, 2023)
Health funding is essential to ensure access to health services. Over time, essentially in the last two decades, the mix of health funding in developed countries has changed. Thus, it is necessary to know this reality and evaluate how the type of funding is vital to ensure access to health services and to continue health coverage worldwide. Around the world, there are significant variations in the amount of financial resources countries spend on health. Therefore, the research aims to identify and quantify which macroeconomic factors have influenced the evolution of health financing in these economies over time. To identify and quantify which macroeconomic and demographic factors influence the evolution of the health funding ratio (specifically the ratio of public and private funding) in 36 countries from 2000 to 2019. The econometric methodology of panel data is applied. For estimating the models, annual statistical information is used for the 36 savings under study in the time scale. It is concluded that health funding through public spending has been decreasing while private spending has been increasing. It was also verified that sociodemographic factors do not influence health financing expenditure. Instead, socioeconomic factors make a significant contribution to health funding. The following variables: population used, unemployment rate, per capita income and inflation rate are statistically significant for the ratio under study.
Keywords: Health financing; public-private expenditure ratio; panel data models; OECD